Пристрої примусової зупинки автомототранспорту: сучасний стан та перспективи розвитку - Губарєв, Г. Г.; Hubariev, H. H. (Право і безпека. - 2013. - № 2 (49). - С. 119-126, 2013)
Розглянуто два напрямки в розвитку засобів примусової зупинки транспорту – вдосконалення раніше розроблених засобів і створення новітніх засобів які враховують нові конструктивні особливості автомобілів та нові уразливі елементи їх конструкції. До найбільш ефективних і безпечних засобів примусової зупинки автотранспорту відносяться запропоновані автором високовольтні пристрої, які базуються на використанні коротких імпульсів електричного струму і магнітних полів, що ці імпульси супроводжують. Такий спосіб примусової зупинки є швидким і значно безпечнішим порівняно з дією інших засобів.

Nowadays the problem of forced stopping of motor transport in law enforcement practice is discussed quite frequently and becomes topical. In spite of normative control of the conditions in which the safe and accident-free use of wellknown forced stopping devices for motor transport is possible, their application quite often results in casualties among involved participants and in damages and material losses. Because of this fact the problem of improvement, development and creation of new safe forced stopping devices for motor transport assumes ever greater importance. There are two ways in development of forced stopping devices for motor transport considered. The first is the improvement and modification of already in use devices. The second one is the creation of latest models taking into consideration the new construction features of automobiles and new weak elements of their construction. The most effective and safe devices of forced stopping are the high-voltage devices, suggested by the author. Functioning of such devices is based on the use of short high-voltage impulses of current and magnetic fields that go with these impulses. Such impulses damage only electronic system of ignition system of engine consumption or on-board computer of automobile. In this case the automobile will be slowing down by the out-of-operation engine without loss of steering capabilities. Such forced stopping will be fast and much safer in comparison with the use of other devices.

Рассмотрены два направления в развитии средств принудительной остановки автомототранспорта – усовершенствование ранее разработанных средств и создание новейших средств, которые учитывают новые конструктивные особенности автомобилей и новые поражаемые элементы их конструкции. К наиболее эффективным и безопасным средствам принудительной остановки автомототранспорта относятся предложенные автором высоковольтные устройства, которые базируются на использовании коротких высоковольтных импульсов электрического тока і магнитных полей, которые эти импульсы сопровождают. Такой способ принудительной остановки является быстрым и значительно более безопасным, в сравнении с использованием других средств.
Forced stopping devices to stop motor transport: present situation and prospectives of development
Устройства принудительной остановки автомототранспорта: современное состояние и перспективы развития
Keywords: транспортні засоби; примусова зупинка; механічні засоби примусової зупинки; електромагнітний імпульс; високовольтні пристрої; імпульс електричного струму; електронні системи автомобіля; motor transport; forced stopping; mechanical devices of forced stopping; electromagnetic impulse; high-voltage devices; electric current impulse; vehicle electronic systems; транспортные средства; принудительная остановка; механические средства принудительной остановки; электромагнитный импульс; высоковольтные устройства; импульс электрического тока; электронные системы автомобиля